1964
DOI: 10.1099/00221287-37-3-341
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Transformation of Neisseria catarrhalis by Deoxyribonucleate Preparations having Different Average Base Compositions

Abstract: SUMMARYThe base contents of deoxyribonucleate (DNA) preparations from 7 strains of Neisseria catarrhalis were determined chromatographically.Three non-overlapping classes were distinguished by mole yo guanine + cytosine. These centred about the values 41 yo (2 strains), 42.3 yo (4 strains, including ATCC 8193), and 44.5 yo (strain NCTC 4103). Each of the 7 strains was capable of undergoing genetic transformation. DNA preparations from spontaneous streptomycin-resistant mutants of all 7 strains elicited transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1965
1965
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 6 publications
2
30
0
Order By: Relevance
“…Results of transformation experiments and DNA base determinations made elsewhere (Catlin, 1960(Catlin, , 1961Catlin & Cunningham, 1961 ;Marmur, Falkow & Mandel, 1963) and on our own strain material (summarized by Barvre, 1967) indicate that Neisseria species can be divided in two subgroups. One subgroup consisting of Neisseria gonorrhoeae, N .…”
Section: Relations Hips With In Neisseriamentioning
confidence: 99%
See 1 more Smart Citation
“…Results of transformation experiments and DNA base determinations made elsewhere (Catlin, 1960(Catlin, , 1961Catlin & Cunningham, 1961 ;Marmur, Falkow & Mandel, 1963) and on our own strain material (summarized by Barvre, 1967) indicate that Neisseria species can be divided in two subgroups. One subgroup consisting of Neisseria gonorrhoeae, N .…”
Section: Relations Hips With In Neisseriamentioning
confidence: 99%
“…The results of recent studies on the relationships of organisms belonging to the genera Moraxella and Neisseria (Barvre, 1967;Catlin & Cunningham, 1961 indicate that a revision of the taxonomy of these organisms is desirable. Transformation experiments and determination of DNA base composition have given particularly suggestive results.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators have reported on the value of esterase electrophoretograms in the characterization of bacterial groups such as the P-haemolytic streptococci (Lund, I corynebacteria (Robinson, I 968), and phytopathogenic bacteria (El-Sharkawy & Huisingh, 1971a, b>. The differences in the characteristics of the esterase isoenzyme patterns from ATCC23246 and the type strain ATCC25238 provides additional evidence that ~~~~2 3 2 4 6 is sufficiently distinct physiologically and in some of its other properties (Catlin & Cunningham, 1964;LaMacchia & Pelczar, 1966;Baumann et al 1968;Fox & McClain, 1974) The existence of an esterase activity band at Mf 0.70 to M f 0.705 in the patterns from the atypical neisserias A~cC19576, A T C C I~~~~ and ATCC 14659, and also B. catarrhalis strains ATCC25238 and A~cC23246 (excluding its acetate pattern) further advances the view of an identifiable intrageneric specificity among these species. Since the electrophoretograms resolved from A~cc19576 and A T C C I~~~~ were virtually indistinguishable they have been recognized here as a single taxonomic entity ( A T c c I~~~~) .…”
Section: Discussionmentioning
confidence: 90%
“…Catlin and Cunningham (5) reported N. catarrhalis to be an atypical neisseria based on its deoxyribonucleic acid (DNA) base composition of 4 1% guanine plus cytosine (G + C) compared to 50% G + C for other neisseriae and by its negligible interspecies transformation frequencies. However, high transformation frequencies between strains of this species were reported (6). Later evidence demonstrated a phenotypic homogeneity among the strains of N .…”
mentioning
confidence: 99%